Understanding Modern Warfare - Jordan, David [et al.] (Cambridge Cambridge University Press, 2016)
A fully revised and updated new edition of the leading introduction to the theory and conduct of warfare.
Include Illustrations, Boxes, Tables, Glossary and Index.
Keywords: Military art and science -- Military history, Modern